RhBMP-2-loaded Poly(lactic-co-glycolic acid) microspheres fabricated by coaxial electrospraying for protein delivery. Issue 18 (12th December 2017) - Zhang, Mei; Ma, Yali; Li, Rongjun; Zeng, Jiehui; Li, Ziqi; Tang, Yajun; Sun, Dahui
Abstract: In this study, we fabricated recombinant human bone morphogenetic protein-2 (rhBMP-2) loaded Poly(lactic-co-glycolic acid) (PLGA) microspheres with core–shell structures and particle sizes ranging from 2.5 to 8 μm by coaxial electrospraying. The manufacturing process of core–shell microspheres by coaxial electrospraying is simpler than that with other methods, and a smaller diameter can be obtained. The microspheres were analyzed by environmental scanning electron microscopy, transmission electron microscopy (TEM), and laser scanning confocal microscopy (LSCM). Moreover, the drug release profiles and degradation of rhBMP-2-loaded PLGA microspheres in vitro were investigated for 21 days and for 7 weeks, respectively. The rhBMP-2 was stabilized by using bovine serum albumin (BSA) to ensure protein activity in the electrospraying process. Fluorescently labeled protein that was loaded into the core–shell PLGA microspheres was verified by LSCM. The distinct layered structure that existed in the manufactured core–shell microspheres can be observed by TEM. Cell Counting Kit-8 (CCK-8) indicated that the core–shell PLGA microspheres loaded with rhBMP-2 have great potential for the treatment of bone defects, for bone regeneration, and in bone tissue engineering.